2012
DOI: 10.1111/j.1365-2664.2012.02165.x
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting avian vision with aircraft lighting to reduce bird strikes

Abstract: Summary1. Bird-aircraft collisions (bird strikes) represent a substantial safety concern and financial burden to civil aviation world-wide. Despite an increase in the rate of damaging bird strikes, necessary steps to develop a mitigation method outside of the airport environment have not been empirically tested. 2.We assessed whether use of aircraft lighting might enhance detection of and reaction to the approach of an aircraft in flight by Canada geese Branta canadensis Linnaeus, a species responsible for a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
81
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 65 publications
(93 citation statements)
references
References 30 publications
1
81
1
Order By: Relevance
“…bird-aircraft collisions, some highways). In the latter scenario, it is conceivable that by enhancing detection of an approaching vehicle, avoidance behaviours could be initiated sooner [28,48,49]. For example, the activation of pulsating lights on aircraft could lengthen AD [49], possibly leading to an increase in FID and thus an enhanced probability of survival during encounters with vehicles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…bird-aircraft collisions, some highways). In the latter scenario, it is conceivable that by enhancing detection of an approaching vehicle, avoidance behaviours could be initiated sooner [28,48,49]. For example, the activation of pulsating lights on aircraft could lengthen AD [49], possibly leading to an increase in FID and thus an enhanced probability of survival during encounters with vehicles.…”
Section: Discussionmentioning
confidence: 99%
“…Irrespective of the mechanism employed, our findings provide a framework and methodological approach to further investigate how different management strategies (e.g. lights on vehicles, vehicle coloration; [49,50]) affect the sensory and behavioural abilities of animals to assess risk and initiate escape in time to avoid collisions with modern vehicles. Data accessibility.…”
Section: Discussionmentioning
confidence: 99%
“…The UVS system is found in the Paleognathae, Passeriformes (Passerida only, not Tyrannida or Corvida), Psittaciformes, and Laridae, with all other diurnal species currently presumed to have a VS system (Ödeen et al 2011). Behavioral studies with VS species have shown that regardless of the SWS1 k max , UV sensitivity may extend to at least 360 nm (Parrish et al 1981(Parrish et al , 1984Blackwell et al 2012).…”
mentioning
confidence: 99%
“…It will therefore be important to take into account avian visual ecology when designing mitigation measures (Martin 2011). Blackwell and Bernhardt (2004) and Blackwell et al (2009Blackwell et al ( , 2012 empirically showed that birds' visual systems (visual acuity and visual fields) enable them to respond behaviourally to lighting regimes (no, constant or pulsating lights) in approaching objects (aircraft and vehicle). Birds have tetrachromatic colour vision and spectral sensitivities of photoreceptors between 320 and 700 nm (Osorio and Vorobyev 2008).…”
Section: Open Accessmentioning
confidence: 99%